(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
This research aims to determine students’ surface difficulties in speaking English and students’ perceptions in the learning process. To collect data. Researchers prepare action plans, implement actions, and reflect on each cycle. At the planning stage, the researcher has prepared a lesson plan, pre-test, post-test, observation checklist, and questionnaire. In taking action, researchers identify and investigate problems that occur in the English language learning process. The results of this research were pretest 39%, test progress 59%, and posttest 84%. From these results, it is summarized that students’ speaking skills have improved.